Writing the Field Recording : Sound, Word, Environment - Benson, Stephen; Montgomery, Will (Edinburgh University Press, 2018)
The 11 essays collected here take the recent explosion of interest in field recordings as the point of departure for an investigation of the sound field in music and its relationship to literature and writing.